ANALYSIS OF THE BUSINESS INCOME AND WELFARE LEVEL OF THE CATTLE FARMERS IN THE DISTRICT OF PAMEKASAN - Widyananda, Cepryana Sathalica; Shamad, Zulfaini (JURNAL AGROSAINS : Karya Kreatif dan Inovatif, 2024)
The income level of cattle farmers in Pamekasan Regency is still relatively low, so it is necessary to conduct research to determine the level of income and welfare of cattle farmers in Pamekasan Regency. The method used in this study is to use a simple random sampling technique of 60 farmers/respondents. The data obtained were tabulated and analyzed quantitatively and qualitatively (business income, household income and welfare level). The results showed that the highest annual income of cattle farmers in Pamekasan Regency was Rp185,750,000 and the lowest income was Rp3,020,000, so it can be said that the cattle business of all respondents experienced profits and the business was feasible with an R/C ratio > 1. The household income of farmers was Rp2,276,126 per month, categorized as a medium income group. The welfare level of cattle farmer households in Pamekasan Regency is 77% (46 people), the majority of which are categorized as prosperous.